Whole-transcriptome analyses of sheep embryonic testicular cells infected with the bluetongue virus - Lu, Danfeng; Li, Zhuoyue; Zhu, Pei; Yang, Zhenxing; Yang, Heng; Li, Zhanhong; Li, Huachun; Li, Zhuoran (Frontiers in Immunology, 2022)
Bluetongue virus (BTV) infection triggers dramatic and complex changes in the host’s transcriptional profile to favor its own survival and reproduction. To systematically understand these changes, here we performed whole-transcriptome sequencing in BTV serotype 1 (BTV-1)-infected and mock-infected sheep embryonic testicular cells, and subsequently conducted bioinformatics differential analyses. In total, 1504 differentially expressed mRNAs, 78 differentially expressed microRNAs, 872 differentially expressed long non-coding RNAs, and 59 differentially expressed circular RNAs were obtained. Gene Ontology annotation, Kyoto Encyclopedia of Genes and Genomes enrichment, and constructed competing endogenous RNA networks indicated differentially expressed RNAs mainly related to virus-sensing and signaling transduction pathways, antiviral and immune responses, inflammation, as well as development and metabolism related pathways. Protein-protein interaction network analysis found that BTV may contribute to abnormal spermatogenesis by reducing steroid biosynthesis. Finally, real-time quantitative PCR results showed that the expression trends of differentially expressed RNAs were consistent with the whole-transcriptome sequencing data. This study provides more insights of comprehensive characterization of BTV-host interactome, and BTV infection and pathogenic mechanisms.